The Biological Activity of Eucalyptus rostrata Leaves Extraction against E.coli and Staphylococcus aureus isolated from Iraqi Patients - Ali, Layla Fouad; Hussein, Nagham Shakir Mohammed (Iraqi Journal of Science, 2018)
The inhibitory effect of Eucalyptus rostrata leaves extraction was investigated on multiple-antibiotic-resistant pathogenic bacteria (E.coli and S. aureus), isolated from Iraqi patients. The minimum inhibitory concentrations in a final concentration of 10 mg/ml. Tow fold dilutions was done from (12.5- 100) mg/ ml to examine the antibacterial effect of different concentrations of the plant extract on both bacteria. The study results revealed that Eucalyptus rostrata extract has a potential inhibitory effect on both gram negative and gram positive species. The current study supports the traditional approach of using Eucalyptus rostrata leaves extraction in treatment trails against bacterial infections.